New Considerations of Early Byzantine Belt Buckles of the "Bologna/Balgota" Type (Archaeologia Adriatica, 2008)
Belt buckles are among the most characteristic early Byzantine finds, whose importance is also emphasized by the fact that often they are the only artifacts that can enable the dating of a broader archaeological context. Their chronology and typology are well known primarily thanks to the works of J. Werner, D. Csallany, and Z. Vinski. In this article, the belt buckles of the "Bologna/Balgota" type are analyzed, more exactly particular variants of these buckles characteristic for southern Italy and the southern Adriatic that the author identifies on the basis of published, but also as yet unpublished material. A total of 16 examples of such buckles are known, and for 13 of these the exact site of discovery is known. Six examples come from Calabria, three from Puglia, two from Drač in northern Albania, and one each from Sicily and from Polače on the island of Mljet. Their basic characteristic is a buckle mount decorated with a cross-like motif in a perforated technique. Considering the great mutual similarity of these buckles and the fact that all were found in places under Byzantine dominion, exclusively in the region of the southern Adriatic and in southern Italy, the author considers it justified to identify this group of buckles as a special variant of the "Bologna/Balgota" type.The buckles are dated to the 7th century, as is proven by examples found in closed grave units together with numismatic material (coins of Heraclius and Constans II), and by other buckles dated to the same period (such as buckles of the "Corinth" type). Such an assignment is further supported by the fact that the "classical" examples of buckles of the "Bologna/Balgota" type are also dated to the 7th century.The belt buckles analyzed in this article indirectly prove the existence of an early Byzantine cultural circle that included the area of the southern Adriatic and southern Italian coasts, at a time when the sea connected and did not divide this territory.
Keywords: belt buckles of the "Bologna/Balgota" type; southern Adriatic; southern Italy; early Byzantine period; 7th century